Cocatalyst‐Free Hybrid Ionic Liquid (IL)‐Based Porous Materials for Efficient Synthesis of Cyclic Carbonates through a Cooperative Activation Pathway. Issue 5 (2nd February 2017) - Jayakumar, Sanjeevi; Li, He; Zhao, Yaopeng; Chen, Jian; Yang, Qihua
Abstract: Cocatalyst‐free ionic liquid (IL)‐based porous polymers (P x ‐V y ‐OH z R) functionalized with an intermolecular hydroxyl group were prepared by means of radical copolymerization of 1‐butyl‐3‐vinylimidazolium bromide, (4‐vinylphenyl)methanol (VBzOH), and divinylbenzene (DVB) under solvothermal conditions. As the ratio of 4‐vinylphenylmethanol in the initial mixture increased, the content of the hydroxyl groups in the polymer increased from 3.35 to 5.35 mmol g −1 and the Brunauer–Emmett–Teller (BET) surface area of the polymer decreased sharply from 365 to 2.5 m 2 g −1 . In the carbonation of CO2 and epoxides, the turnover frequency (TOF) of P x ‐V y ‐OH z R increased gradually from 25 to 67 h −1 as the OH ratio increased irrespective of the sharp decrease in BET surface area, which suggests the existence of a cooperative activation effect between OH and ILs. To obtain a high OH content while still maintaining a high BET surface area, hybrid porous materials (SBA‐[V x OH y ]R‐ n ) were prepared by means of copolymerization of 1‐ethyl‐3‐vinylimidazolium bromide and 4‐vinylphenylmethanol in the mesopores of SBA‐15. SBA‐[V x OH y ]R‐ n was more active than its polymer counterpart (TOF: 188 versus 71 h −1 ) in the cycloaddition of CO2 with propyl oxide owing to the combined effect of the high BET surface area and the high OH content. The hybridization of mesoporous materials with polymers represents an efficient strategy for the preparation of high‐performance solid catalysts for chemical transformations. Abstract : Stronger together : An ionic liquid (IL)‐based polymer and allyl‐modified mesoporous silica (SBA‐15) hybrid material functionalized with an intermolecular hydroxyl group were synthesized. In the carbonation of CO2 and epoxides, polymers that contain both ILs and OH show higher activity than polymers that contain only ILs, which suggests a cooperative effect of OH and ILs (see figure).